2011
DOI: 10.4021/jcs101e
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hospital Mortality and Epidemiology in Trauma Patients: A Multi-Center Study

Abstract: Background: This study evaluated the clinical characteristics of trauma patients in the southeastern coastal area of Turkey and investigated the factors influencing mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 14 publications
6
13
0
6
Order By: Relevance
“…The most common cause of trauma injuries in our study was motor vehicle accidents (motorcycle, car, pedestrian, bus) and fall from height, which was consistent with the findings of the study performed in Turkey (17). Moreover, motor vehicle accidents were the leading cause of injury in the patients younger than 60 years, while fall from height was the major cause in those over 60 years old.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The most common cause of trauma injuries in our study was motor vehicle accidents (motorcycle, car, pedestrian, bus) and fall from height, which was consistent with the findings of the study performed in Turkey (17). Moreover, motor vehicle accidents were the leading cause of injury in the patients younger than 60 years, while fall from height was the major cause in those over 60 years old.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, elderly patients comprised a considerable proportion of patients which is similar to the results of the studies conducted in Turkey, India, and Greece as well as to the reports provided by WHO (12)(13)(14)(15). The sex ratio in our center was similar to that of the previous studies performed in other developing countries (14,(16)(17)(18). However, sex ratio was reported as 4.2 by a survey conducted in Tehran (the capital city of Iran) in 2004, which may reflect a change in incidence of injuries in recent years (19).…”
Section: Discussionsupporting
confidence: 87%
“…It is a well-known fact that trauma mostly affects the youth, particularly the third and fourth decades (12,13) . In our study, the mean age was 33.7±11.9 year, 55% were in age group between 20-40 years and males comprised (78%.3) of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sogut O et al, had studied the Injury trends and mortality in adult patients with major trauma in New South Wales. They found that the percentage of in hospital deaths were 13.6% when severe polytraumatized patients were selected (13) . Regarding the effect of age on mortality, in our study the mortality rate increases with age as 43% of death occurred in patients in age group (50-60) with statistically significant relation (P=0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who presented within one hour of injury were more likely to die than those who presented after one hour, OR=0.23 (95% CI 0.07-0.80) and P=0.021. Other studies have reported reduced mortality in patients who present within one hour of injury ('the Golden hour') [22,23]. This difference could be explained by the injury characteristics of these patients and their inhospital management.…”
Section: Distribution Of Factors Which Are Known To Affect Outcomementioning
confidence: 95%